Use and consequences of exercise tracking technology on exercise psychopathology and mental health outcomes in adolescents - Kalli A Reynolds; Emma Haycraft; Carolyn R Plateau (International Journal of Adolescence and Youth)
Exercise tracking technology use is associated with exercise psychopathology in adolescents; however, research is yet to identify components of such technology that can predict maladaptive exercise at this age. This research assessed the relationship between exercise tracking technology use and exercise psychopathology in adolescents. Development of a new measure of exercise tracking behaviours/attitudes was also conducted. Adolescents (N = 327; aged 12–15, mean = 13.64 years (SD = .95); n = 168 girls) participated in this multi-phase study. Following factor analysis to develop and validate the new measure, relationships between exercise tracking behaviours/attitudes and compulsive exercise were explored. Key components of such technology (e.g. pressure to achieve exercise-related goals) were significantly associated with higher compulsive exercise in adolescents. However, using technology to simply monitor their own exercise behaviours was significantly associated with positive exercise and mental wellbeing outcomes. Prospective research should assess how exercise tracking can predict exercise psychopathology changes and mental wellbeing throughout adolescent development.